Discarded plasma obtained after cord blood volume reduction as an alternative for fetal calf serum in mesenchymal stromal cells cultures. Issue 9 (6th August 2020) - Vlaski‐Lafarge, Marija; Chevaleyre, Jean; Cohen, Julie; Ivanovic, Zoran; Lafarge, Xavier
Abstract: BACKGROUND: Utilization of the fetal calf serum (FCS) carries a potential health risk and raises growing economic and ethical problems. Umbilical cord blood volume reduction, required for banking, provides clinical‐grade umbilical cord blood plasma (UCBP) discarded as a waste. The aim of this study was to test whether serum derived from UCBP could replace FCS for the amplification of mesenchymal stromal cells (MSCs). STUDY DESIGN AND METHODS: To this end, the amplification of the MSCs and mesenchymal progenitors was estimated in the presence of serum derived from UCBP and its cytokine content was determined by cytometric bead array and enzyme‐linked immunosorbent assay techniques. As a comparison, other sources of clinical‐grade human serum were tested in parallel: serum derived from solvent/detergent–treated fresh‐frozen plasma (S/D‐FFP) and from platelet (PLT)‐rich and PLT‐poor umbilical plasma. RESULTS: Serum derived from UCBP‐supplemented culture sustains identical amplification of MSCs and their progenitors as in the case of FCS addition. Furthermore, the assays reveal the presence in the serum derived from UCBP of cytokines influencing the properties of MSCs (basic fibroblast growth factor, transforming growth factor‐β, vascular endothelial growth factor, and interleukin‐8) or involved in the development of the myeloid lineage (thrombopoietin, erythropoietin, granulocyte–colony‐stimulating factor, and granulocyte‐macrophage–colony‐stimulating factor). Also, our study indicates important differences between neonatal and adult‐derived serum. Poor cytokine content in the S/D‐FFP makes a less efficient replacement of FCS comparing to other human blood–derived supplements. CONCLUSION: Our work shows that the discarded human cord blood plasma from volume reduction is an easily obtainable and greatly available, xeno‐free source of serum that is a highly efficient replacement of FCS in sustaining MSC growth.